2018
DOI: 10.1089/jmf.2017.3990
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus acidophilus Improves Intestinal Inflammation in an Acute Colitis Mouse Model by Regulation of Th17 and Treg Cell Balance and Fibrosis Development

Abstract: Disruption of the balance among the microbiota, epithelial cells, and resident immune cells in the intestine is involved in the pathogenesis of inflammatory bowel disease (IBD). Probiotics exert protective effects against IBD, and probiotic commensal Lactobacillus species are common inhabitants of the natural microbiota, especially in the gut. To investigate the effects of Lactobacillus acidophilus on the development of IBD, L. acidophilus was administered orally in mice with dextran sodium sulfate (DSS)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 34 publications
7
83
0
Order By: Relevance
“…The improvement of culture-independent and molecular high-throughput techniques favor the identification of previously unknown bacteria, which would provide novel insights into the functional capacity and compositional diversity of some of the fecal microbiota. In addition, several studies have suggested that disorders such as colorectal cancer, inflammatory bowel disease (IBD), alcoholic and nonalcoholic fatty liver diseases, obesity, type 2 diabetes, oxidative stress–related disease, and immune-mediated diseases are associated with disease-specific dibiotic of altered microbiota compositions [ 15 , 39 43 ]. Modification of the gut microbiota has thus gained more attention as a potential treatment for several diseases in humans and animals.…”
Section: Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement of culture-independent and molecular high-throughput techniques favor the identification of previously unknown bacteria, which would provide novel insights into the functional capacity and compositional diversity of some of the fecal microbiota. In addition, several studies have suggested that disorders such as colorectal cancer, inflammatory bowel disease (IBD), alcoholic and nonalcoholic fatty liver diseases, obesity, type 2 diabetes, oxidative stress–related disease, and immune-mediated diseases are associated with disease-specific dibiotic of altered microbiota compositions [ 15 , 39 43 ]. Modification of the gut microbiota has thus gained more attention as a potential treatment for several diseases in humans and animals.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Furthermore, the gut microbiota composition is likely to affect many organ systems, including the cardiovascular, neural, immune, and metabolic systems. The gut microbiota composition is altered in many disease states, such as cardiovascular disease, cancer, malignancy, type 2 diabetes mellitus, obesity, colitis, asthma, psychiatric disorders, inflammatory disorders, disorders of the gut-brain axis, and numerous immune disorders [ 15 , 40 , 41 , 46 48 ]. Modulation of the gut microbiota facilitates a number of health problems; probiotic feeding with a high-fat diet showed alteration of the gut microbiota composition with a decrease in the gram-positive bacteria phyla Firmicutes and Actinobacteria in mice [ 49 ].…”
Section: Modulation Of Gut Microbiota and Probiotic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Like several of the previous species, it reduces high-fat diet induced obesity and improves insulin resistance 46 . It also demonstrates an anti-inflammatory effect, protecting mice from induced colitis 50,51 . In humans, L. acidophilus has been observed to be significantly reduced in the feces of type 2 diabetics 52 .…”
Section: Genus Lactobacillus (Lactic Acid Bacteria)mentioning
confidence: 99%
“…TrkB-PLC/IP3 pathway is mainly consisted of protein-tyrosine kinase receptor B (TrkB), phospholipase C (PLC) and inositol triphosphate (IP3). After the specific binding of brain-derived neurotrophic factor (BDNF) to TrkB, TrkB is phosphorylated to p-TrkB, which activates the signal transduction of PLC/IP3 in the downstream, thereby playing roles in the increase of intracellular Ca 2+ concentration, the enhancement of nerve-muscle excitation conduction, the promotion of cell mobility in the intestinal smooth muscle, and the promotion of intestinal motility [14][15][16][17][18][19]. At present, there is no research showing the regulatory mechanism of TrkB-PLC/IP3 pathway on colitis.…”
Section: Introductionmentioning
confidence: 99%